2021
DOI: 10.1186/s13075-020-02406-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the proportion of clinical clusters contribute to the phenotypic evolution of Behçet’s disease in Japan

Abstract: Background We hypothesized that Behçet’s disease (BD) consists of several clinical subtypes with different severity, resulting in heterogeneity of the disease. Here, we conducted a study to identify clinical clusters of BD. Methods A total of 657 patients registered in the Yokohama City University (YCU) regional BD registry between 1990 and 2018, as well as 6754 patients who were initially registered in the Japanese Ministry of Health, Labour and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 49 publications
9
44
1
Order By: Relevance
“…Second, certain demographic analysis does not support a link between manifestations of BD form FIGURE 1 | Systemic inflammation leading to clinical features in Behcȩt's disease may either be initiated by of causing changes in the gut microbiome in patients who are genetically predisposed to the condition. example ocular involvement not associated with intestinal BD (13). Thirdly, many patients with BD do not have intestinal-BD, therefore there is no direct association between gut inflammation, the microbiome and other manifestations of BD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, certain demographic analysis does not support a link between manifestations of BD form FIGURE 1 | Systemic inflammation leading to clinical features in Behcȩt's disease may either be initiated by of causing changes in the gut microbiome in patients who are genetically predisposed to the condition. example ocular involvement not associated with intestinal BD (13). Thirdly, many patients with BD do not have intestinal-BD, therefore there is no direct association between gut inflammation, the microbiome and other manifestations of BD.…”
Section: Discussionmentioning
confidence: 98%
“…To identify the clinical clusters of BD, Soejima and associates investigated the clinical phenotype of 657 patients with BD from the Yokohama City Hospital database and 6754 patients with BD from the Japanese Ministry of Health, Labour and Welfare database. They identified that gastrointestinal BD was associated with vascular but not eye involvement, while a second cluster had high incidence of eye involvement but no vascular or neurological involvement (13). Chronological analyses showed expansion of the gastrointestinal cluster in BD patients over 27 years in a relatively stable genetic cohort in Japan, indicating that environmental factors might be involved in the disease manifestation of BD.…”
Section: Gut and Oral Microbiomes In Bd-summarymentioning
confidence: 99%
“…There is accumulating evidence that HLA-B∗51 positivity differs among the clinical subtypes of Behçet's syndrome [ 14 ▪ , 21 , 22 , 23 ▪ ]. Maldini et al conducted meta-analyses to determine the relationship of the HLA-B5 or B∗51 genotype with each clinical symptom in patients with Behçet's syndrome [ 14 ▪ ].…”
Section: Clinical Implication Of Hla-b∗51mentioning
confidence: 99%
“…Recently, the frequency of HLA-B51 has been declining in Japanese patients with Behçet's syndrome [ 21 , 23 ▪ ]. This decline has been associated with an increased ratio of female patients, increased gastrointestinal involvement, and decreased ocular disease.…”
Section: Clinical Implication Of Hla-b∗51mentioning
confidence: 99%
See 1 more Smart Citation